2012
DOI: 10.1371/journal.pone.0042090
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Breeding of a Fungus Producing a Precursor Diterpene Suitable for Semi-Synthesis by Dissection of the Biosynthetic Machinery

Abstract: Many clinically useful pharmaceuticals are semi-synthesized from natural products produced by actinobacteria and fungi. The synthetic protocols usually contain many complicated reaction steps and thereby result in low yields and high costs. It is therefore important to breed microorganisms that produce a compound most suitable for chemical synthesis. For a long time, desirable mutants have been obtained by random mutagenesis and mass screening. However, these mutants sometimes show unfavorable phenotypes such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…27,28) Blocked mutants as well as gene deletion mutants provide not only clues to the identification of key steps in the biosynthetic pathway but also biosynthetic intermediates and shunt metabolites, which normally are present only in very small amounts in wild-type cultures. [28][29][30] In fact, the metabolite profile of Af293 gave us a hint as to previously unknown metabolite 4.…”
Section: Discussionmentioning
confidence: 99%
“…27,28) Blocked mutants as well as gene deletion mutants provide not only clues to the identification of key steps in the biosynthetic pathway but also biosynthetic intermediates and shunt metabolites, which normally are present only in very small amounts in wild-type cultures. [28][29][30] In fact, the metabolite profile of Af293 gave us a hint as to previously unknown metabolite 4.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes responsible for oxidative modification of the hydrocarbon scaffold were subsequently biochemically characterized [188]. Later, a second gene cluster was identified that encodes nine additional genes needed for the biosynthesis of fusicoccin A [189] (Fig. 8).…”
Section: Fusicoccanes and Other Diterpenoids Made By Monofunctional Ementioning
confidence: 99%
“…This cluster was identified in the draft genome sequence of P. amygdali based on a previously identified ABBA-type prenyltransferases that catalyzed in vitro the reverse O-prenylation of glucose with DMAPP [70], which is a prenylation that is also present in fusiccocin A. A combination of in vitro assays with recombinant enzymes and gene disruption allowed Dairi's group to then establish the complete fusicoccin A pathway [189]. His group also identified and functionally characterized the brassicicene C biosynthetic pathway from A. brassicola, which includes, in addition to a fusicoccadiene synthase (AbFs), a dioxygenase and oxidoreductase as well as five P450s [188,190,191].…”
Section: Fusicoccanes and Other Diterpenoids Made By Monofunctional Ementioning
confidence: 99%
“…3) to supply more IPP for indole diterpene biosynthesis was constructed because P. amygdali produced large amounts (>1 g/L) of fusicoccin-related compounds. 34) That strain, however, produced no specific compounds. Then, we focused on a transcriptional regulator, since the activation of transcriptional regulators sometimes results in high production of secondary metabolites in fungi, 35,36) but no candidate genes were located at the flanking regions of the cluster.…”
Section: Resultsmentioning
confidence: 91%
“…1(A)), from the strain we cloned the biosynthetic genes of fusicoccin A. 34) We attempted to identify a compound governed by the cluster, but all attempts failed. The following results, however, suggest that the cluster might be responsible for the biosynthesis of a lolilline/lolitrem type of compound.…”
Section: Discussionmentioning
confidence: 99%